AN ASSESSMENT OF THE EFFECTIVENESS A PHYSICAL CURING METHODS OF MOULDING SAND BONDED BY BINDER BASED ON STARCH AND ALUMINOSILICATES (Metallurgy and Foundry Engineering, 2016)
In this study, based on results of determination selected properties of moulding sand such as permeability, tensile strength and wear resistance, the effectiveness of curing methods: by conventional heating and by innovative of microwave curing were compared. The tested moulding sand used to research was composition of silica sand with a commercial binder in the form of Albertine F/1 (Hüttenes Albertus). This binder is a mixture of swellable in water starch derivatives and aluminosilicates. Binding in the moulding sand was occurred by evaporation of the solvent from samples (water).Based on the obtained results were showed a dependence of the properties of moulding sand and selected methods of physical cure, especially after 1 and 4 hours of cured samples storage. However, after 24 hours of samples storage, as apparent from the analysis of the obtained results, both used curing methods are almost the same effective, and marked differences in the properties of the moulding sands were located in the range of measurement uncertainty. Using electromagnetic waves in the microwave range was possible significantly reduce the time of curing and the energy of the drying process.